1993
DOI: 10.1007/bf02770627
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid Interleukin-8 as a marker for intraamniotic infection

Abstract: We measured the amniotic fluid Interleukin-8 (AF IL-8) levels of 80 women to see whether or not AF IL-8 levels were of value in the diagnosis of intraamniotic infection. Of twelve patients developing conventional signs of infection, 9 had an AF IL-8 concentration above 10,000 pg/ml serum. In two patients, whose baby had a serious neonatal infection, AF IL-8 concentration also exceeded 10,000 pg/ml. Only one out of 66 apparently uninfected patients had an AF IL-8 level above 10,000 pg/ml. We therefore suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…16.0, 14.0Ϫ33.1 pg/ml vs. 13.2, 10.6Ϫ 17.6 pg/ml in non infection group, p < 0.05). No significant difference was noticed in cord blood concentrations of G-CSF and IL-8 during histologic chorioamnionitis or in early-onset neonatal…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…16.0, 14.0Ϫ33.1 pg/ml vs. 13.2, 10.6Ϫ 17.6 pg/ml in non infection group, p < 0.05). No significant difference was noticed in cord blood concentrations of G-CSF and IL-8 during histologic chorioamnionitis or in early-onset neonatal…”
mentioning
confidence: 84%
“…Amniotic fluid levels have been shown to predict vascular extension of chorioamnionitis and neonatal infection [1,3,5,15,16,21,25]. Amniotic fluid levels have been shown to predict vascular extension of chorioamnionitis and neonatal infection [1,3,5,15,16,21,25].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to IL-6, elevated IL-8 levels have also been associated with clinical or histological signs of intrauterine infection 61 (Table 3 [B]). IL-8 is significantly increased during labor, but even higher values have been detected when labor was associated with positive amniotic fluid cultures 59 (Table 3 [B]).…”
Section: Amniotic Fluidmentioning
confidence: 99%
“…[8] The positive correlation between maternal and cord serum IL-8 levels was found to be useful for rapid prenatal screening of chorioamnionitis at term. [8] The positive correlation between maternal and cord serum IL-8 levels was found to be useful for rapid prenatal screening of chorioamnionitis at term.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 8 (IL-8), a CXC chemokine produced by various types of cells including monocytes/macrophages, eosinophils, T-cells, NK cells, fibroblasts, endothelial cells, keratinocytes, hepatocytes, astrocytes, chondrocytes, and neutrophils upon stimulation with proinflammatory stimuli, exerts a variety of functions particularly on leukocytes. [8,9] The IL-8 molecule was originally reported as 10 kDa protein but later precise determinations have demonstrated that natural IL-8 occurs as a 6-8 kDa doublet. [4] The IL-8 levels in different body fluids very often correlate with the severity of the diseases, as found in bronchoalveolar lavage of patients with acute respiratory distress syndrome, [5] in plasma of patients with multiple organ failure, [6,7] and in amniotic fluid during intraamniotic infections.…”
Section: Introductionmentioning
confidence: 99%